Formulation and evaluation of Diphenhydramine hydrochloride and Ibuprofen soft gelatin capsules - Shyamala Bhaskaran, Pradeep GC, Lakshmi PK (Journal of Applied Pharmaceutical Science)
The present invention provides a new composition for treating pain-associated sleep disturbances, especially shortened sleep duration, comprising ibuprofen and diphenhydramine hydrochloride. In the present work the soft gelatin capsules were formulated comprising 25 mg diphenhydramine hydrochloride and 200 mg ibuprofen using polyethylene glycol 400, propylene glycol, potassium hydroxide and purified water. The prepared soft gelatin capsules were evaluated for weight variation test, assay, dissolution and disintegration. The capsules had a fill weight of 550 ± 5%, Disintegration time of 5-6 minutes and showed 97.00% to 99.50% of labeled amount of ibuprofen and diphenhydramine hydrochloride indicating uniformity in drug contents. The capsules containing 75 mg/capsule of propylene glycol released 99.40% of diphenhydramine hydrochloride and 99.70% of ibuprofen at the end of 60 minutes. Thus, it may be concluded that soft gelatin capsules of diphenhydramine hydrochloride and ibuprofen could be successfully prepared with existing technology and machinery which have a commercial viability and enhance patient compliance with improved bioavailability.
Keywords: Capsule, soft gelatin, diphenhydramine hydrochloride, ibuprofen